A reflective theory of sensitive issues in the Partition of India in the Manohar Malgaonkar’s “A bend in the Ganges.” - Dr Vinay Kumar Chaudhary (JOURNAL OF MANAGEMENT, SCIENCES, OPERATION & STRATEGIES, 2023)
Freedom & violence came to India with each other. The joy of independence was overshadowed by the painful partition of the great land along religious lines as India and Pakistan. In the process, thousands were slaughtered, a great number of women were raped, abducted and mutilated and millions were rendered homeless. Thus, the Partition of India remains a painful, watershed moment in the Indian freedom struggle. The events which led to the partition, the partition itself and its aftermath have captured the imagination of quite a few creative writers. These writers have given faithful and artistic accounts of the partition of the great land of India in their creative works. This has given birth to the genre of 'The Partition Novel. ’The present paper is a critical study of Manohar Malgonkar's A Bend in the Ganges, based on the Partition theme. Keywords: Partition, freedom, independence, religious.